Effect of Baseline Spastic Hemiparesis on Recovery of Upper-Limb Function Following Botulinum Toxin Type A Injections and Postinjection Therapy - Chang, Chia-Lin (Arch Phys Med Rehabil, 2009)
OBJECTIVE: To determine whether baseline hand spastic hemiparesis assessed by the Chedoke-McMaster Assessment influences functional improvement after botulinum toxin type A (BTX-A) injections and postinjection therapy. DESIGN: Prospective cohort study. SETTING: Outpatient spasticity clinic. PARTICIPANTS: Participants (N = 14) with spastic hemiparesis divided into 2 groups: Chedoke-McMaster Assessment Hand-Higher Function (stage≥4, n = 5) and Chedoke-McMaster Assessment Hand-Lower Function (stage = 2 or 3, n = 9). INTERVENTIONS: Upper-limb BTX-A injections followed by 6 weeks of postinjection therapy. MAIN OUTCOME MEASURES: Primary outcomes were Motor Activity Log-28 and Motor Activity Log items. Secondary outcomes were Action Research Arm Test (ARAT), Motor Activity Log-Self-Report, and Modified Ashworth Scale (MAS). Measures were assessed at baseline (preinjection), 6 weeks, 9 weeks, and 12 weeks postinjection. RESULTS: Primary and secondary outcomes improved significantly over time in both groups. Although no significant differences in ARAT or MAS change scores were noted between groups, Chedoke-McMaster Assessment Hand-Higher Function group demonstrated greater change on Motor Activity Log-28 (P = .013) from baseline to 6 weeks and Motor Activity Log items (P = .006) from baseline to 12 weeks compared to Chedoke-McMaster Assessment Hand-Lower Function group. CONCLUSIONS: BTX-A injections and postinjection therapy improved hand function and reduced spasticity for both Chedoke-McMaster Assessment Hand-Higher Function and Chedoke-McMaster Assessment Hand-Lower Function groups. Clinicians should expect to see larger gains for persons with less baseline impairment.